2010
DOI: 10.1074/jbc.m110.129916
|View full text |Cite
|
Sign up to set email alerts
|

Splice Variants of SmgGDS Control Small GTPase Prenylation and Membrane Localization

Abstract: Ras and Rho small GTPases possessing a C-terminal polybasic region (PBR) are vital signaling proteins whose misregulation can lead to cancer. Signaling by these proteins depends on their ability to bind guanine nucleotides and their prenylation with a geranylgeranyl or farnesyl isoprenoid moiety and subsequent trafficking to cellular membranes. There is little previous evidence that cellular signals can restrain nonprenylated GTPases from entering the prenylation pathway, leading to the general belief that PBR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
183
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(188 citation statements)
references
References 51 publications
(83 reference statements)
4
183
1
Order By: Relevance
“…Interestingly, recent results from the Williams laboratory suggest that SmgGDS-558 specifically binds prenylated GTPases in cells, whereas the larger SmgGDS isoform specifically interacts with nonprenylated GTPases (39). As the majority of Rho in cells is expected to be prenylated, this may explain our observation of preferential activation of Rho in cells by SmgGDS-558.…”
Section: Discussionmentioning
confidence: 71%
“…Interestingly, recent results from the Williams laboratory suggest that SmgGDS-558 specifically binds prenylated GTPases in cells, whereas the larger SmgGDS isoform specifically interacts with nonprenylated GTPases (39). As the majority of Rho in cells is expected to be prenylated, this may explain our observation of preferential activation of Rho in cells by SmgGDS-558.…”
Section: Discussionmentioning
confidence: 71%
“…There are two predominant isoforms of SmgGDS, SmgGDS-607 and SmgGDS-558, which differ by one armadillo domain (5). Recent studies have demonstrated that SmgGDS-558 plays a more significant role than SmgGDS-607 in activating RhoA in breast cancer cells, despite lower levels of endogenous SmgGDS-558 protein (6,7).…”
mentioning
confidence: 99%
“…SmgGDS (Rap1GDS1) is a noncanonical GEF for RhoA and RhoC (4) and also promotes the pro-oncogenic functions of several other small GTPases with C-terminal polybasic regions (PBRs) (5). There are two predominant isoforms of SmgGDS, SmgGDS-607 and SmgGDS-558, which differ by one armadillo domain (5).…”
mentioning
confidence: 99%
“…Regulation of the prenylation pathway has been largely unexamined, although the recent finding that entry into, and passage through, the prenylation pathway of some small GTPases can be controlled by specific SmgGDS splice variants has highlighted the potential for control of CaaX protein function via this process (28). These recent developments in the prenylation field, coupled with the genetic evidence in plants for demethylation of prenyl proteins (18,19) and our finding of dynamic control of RhoA methylation by CES1, opens new avenues of investigation into the dynamics of prenyl protein processing.…”
Section: Discussionmentioning
confidence: 99%